1985
DOI: 10.1148/radiology.155.2.3157203
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal coronary angioplasty with an over-the-wire system.

Abstract: The original Gruentzig coaxial catheter system for percutaneous transluminal coronary angioplasty (PTCA) utilized a blunt, closed-end, inner balloon catheter with a short guide wire attached to its tip. Options for safely crossing severe stenoses with this large, nonmaneuverable catheter were limited. More recently, over-the-wire systems have been developed in which the lesion initially is crossed with a small-caliber floppy or steerable guide wire, then by the balloon catheter advanced over the wire. Technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The fixed wire era is reported as the 1977–1982 period in a five-year study comprising 631 patients where successful angioplasty was reported for 59% of stenosed arteries and where 65 of 91 patients (83%) with a one-year follow-up reported overall improved condition; on the other hand, emergency coronary artery bypass was required in six percent of cases, myocardial infarction occurred in four percent, and in-hospital death occurred in one percent (4). The over-the-wire era saw increased success rates associated with an improved catheter design in which the arterial lesion was crossed first by a small-caliber floppy steerable guide wire, then by the balloon catheter that was advanced over the guide wire; because of the improved outcomes, the 1985–1986 Percutaneous Transluminal Coronary Angioplast Registry was re-opened in order to track outcomes (5, 6). The so-called stent era saw success rates improve to 97% with overall improved immediate and one-year outcomes, despite the fact that PCI use had also expanded to include more patients with severe comorbidities, acute coronary syndromes, and complex multi-vessel disease (7).…”
Section: Discussionmentioning
confidence: 99%
“…The fixed wire era is reported as the 1977–1982 period in a five-year study comprising 631 patients where successful angioplasty was reported for 59% of stenosed arteries and where 65 of 91 patients (83%) with a one-year follow-up reported overall improved condition; on the other hand, emergency coronary artery bypass was required in six percent of cases, myocardial infarction occurred in four percent, and in-hospital death occurred in one percent (4). The over-the-wire era saw increased success rates associated with an improved catheter design in which the arterial lesion was crossed first by a small-caliber floppy steerable guide wire, then by the balloon catheter that was advanced over the guide wire; because of the improved outcomes, the 1985–1986 Percutaneous Transluminal Coronary Angioplast Registry was re-opened in order to track outcomes (5, 6). The so-called stent era saw success rates improve to 97% with overall improved immediate and one-year outcomes, despite the fact that PCI use had also expanded to include more patients with severe comorbidities, acute coronary syndromes, and complex multi-vessel disease (7).…”
Section: Discussionmentioning
confidence: 99%